(untitled) (Revista Nacional de Odontología, 2017)
Introduction: Removal of canines is indicated in cases where there is impact on these teeth and the possibilities of orthodontic traction are limited or zero. Diagnosis: It is the case of a 36-year-old patient who comes for consultation because he is not satisfied with the aesthetics of his smile. Treatment: As an alternative treatment in this case, mandibular canines were extracted instead of the first premolars. Discussion: It was possible to improve occlusal relations, overjet, and overbite without damaging the patient’s facial appearance. Whenever strategically convenient, the functional and aesthetic results obtained suggest the possibility of having this alternative as an option in the treatment of our patients. Conclusion: This scheme of extractions then allows to fulfill both functional and aesthetic objectives; however, this should be reserved for cases in which its application is advantageous, until more research is done to guarantee its long-term effects.